Trends of Forensic Analysis of Pen Ink Using Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) Spectroscopy - Putri Nabihah Abdul Khofar; Umi Kalsum Abdul Karim; Ezlan Elias; Muhd Fauzi Safian; Mohamed Izzharif Abdul Halim (Universitas Gadjah Mada, 2022)
Many articles have been published on ink analysis to assist Forensic Document Examiner (FDE) in examining questioned documents. Ink analysis encountered about 45% of ballpoint and 24% of gel pen in forensic cases. Typically, ink samples found on the documents are limited to small quantities, requiring non-destructive techniques to preserve the evidence. Previous studies on ink analysis cover about 80% of spectroscopy techniques, including the Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR). FDE prefers ATR-FTIR to retain the legibility of evidence since ATR-FTIR is known as non-destructive, fast, reliable, and precise instrumentation. Various modifications and developments to this technique have been published. Therefore, this work reviews the trend of analysis performed on samples of the document and evaluates the current approaches to the capacity of using ATR-FTIR on such samples. Remarks on the comparison studies are also included.